(Pro?)-cyclicality of collateral haircuts and systemic illiquidity - Florian Glaser; Sven Panz (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
Procyclicality of collateral haircuts and margins has become a widely proclaimed behavior and is currently discussed not only by academic literature but also by regulatory authorities in Europe. Procyclicality of haircuts is assumed to be a trigger of liquidity spirals due to its tightening effect of collateral portfolio values in times of market distress. However, empirical evidence on this topic is quite sparse and the discussions are primarily driven by insights derived from theoretical models. Nonetheless, oversight bodies are discussing macroprudential haircut add-ons in order to curb with the potential effects of procyclicality in distressed periods. Based on a unique data set provided by a large European Central Counterparty we construct a measure of systemic illiquidity of bond collaterals and analyze the relationship between haircuts, the development of periods with explosive behavior and systemic illiquidity. We estimate the noise of bond yields to measure systemic illiquidity with and without considering haircuts. We then apply an explosive roots bubble detection technique to identify irrational periods of each of these two time series and to a combination of both. Finally, we propose a quantitative trigger and design for macroprudential haircut add-ons. Our results confirm that (1) bond collateral markets face irrational, i.e. bubble-like illiquidity during periods of systemic distress. The results indicate that (2) haircuts are not amplifying or increasing with systemic illiquidity. (3) The proposed haircut add-on mechanism exhibits desirable features to mitigate systemic illiquidity during lasting periods of distress.
Keywords: E44; G18; G01; 330; Procyclicality; Collateral Haircuts; Systemic Risk; Macroprudential Add-On